AB0126 Low prevalence of antibodies against malondialdehyde-acetaldehyde adducts in spanish patients with rheumatoid arthritis. (12th June 2018) - Rodriguez-Martinez, L.; Perez-Pampin, E.; Mera-Varela, A.; Conde, C.; Gonzalez, A.
Abstract : Background: Patients with rheumatoid arthritis (RA) present increased oxidative stress that leads to lipid peroxidation and the formation of malondialdehyde (MDA) and acetaldehyde (AA). These two compounds under oxidative stress form malondialdehyde-acetaldehyde (MAA) adducts with proteins, which are highly immunogenic. Recently, Thiele et al. 1 described the presence of antibodies against human albumin MAA adducts in patients with established RA from the Veterans Affairs Rheumatoid Arthritis (VARA) registry. Of particular relevance was the reported presence of IgG anti-MAA antibodies in 92% of the patients, including 88% of the anti-CCP negative patients. These results suggest MAA adducts could contribute to the pathogenesis of RA and the anti-MAA antibodies could drastically reduce the number of patients with seronegative RA. Objectives: To replicate the association of anti-MAA antibodies with RA and explore their value as biomarkers. Methods: Sera from 515 Spanish patients with established RA that fulfilled the 1987 ACR classification criteria and from 274 healthy controls were included. Available information included history of smoking, anti-CCP status, and genotype of HLA-DRB1 and PTPN22 rs2476601. Human serum albumin MAA adducts and hexyl-MAA standard were chemically synthesised. Anti-MAA antibodies against the albumin MAA adducts were determined by indirect ELISA using isotype-specific secondary antibodies for IgG, IgM and IgA. Results: Anti-MAA antibodies were detected in a small fraction of the RA patients, who had slightly increased antibody titers compared to healthy controls, 6.4% were positive for IgG, 15.7% for IgM and 8.0% for IgA. The low prevalence of anti-MAA antibodies persisted in spite of multiple variations in the ELISA protocols including the use of different albumin sources, albumin MAA adducts produced in two different laboratories, and various secondary antibodies. IgM anti-MAA antibody titers were increased in smokers compared to non-smokers. Moreover, the presence of IgM and of IgA anti-MAA antibodies were associated with anti-CCP and RF positivity. Conclusions: Anti-MAA antibodies were detected in a small fraction of the Spanish RA patients, but their low sensitivity questions the value of these antibodies as biomarkers of RA. Due to the contradictory findings, additional studies should be performed that will need to address also the role of MAA adducts on RA pathogenesis. Reference: [1] Thiele GM, et al. Arthritis Rheumatol2015;67(3):645–55. Acknowledgements: Supported by grants PI14/01651 and RD16/0012/0014 of the Instituto de Salud Carlos III (Spain) that are partially financed by the ERDF Disclosure of Interest: None declared